Bar for assisting in internal irradiation of particles as well as preparation method and application of bar

By preparing chitosan-based sponge rods with water absorption and expansion characteristics and hemostatic properties, the problems of bleeding and particle shift during internal irradiation particles are solved, and rapid hemostatic and particle fixation are achieved, which improves the therapeutic effect and reduces costs.

CN119524192APending Publication Date: 2025-02-28AFFILIATED ZHONGSHAN HOSPITAL OF DALIAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411843057.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

During the intrairradiation particle implantation, bleeding caused by puncture and particle shift lead to misplugging. The prior art is difficult to effectively solve these problems, especially in areas with abundant blood vessels or areas with abundant tumor blood supply.

Method used

Using chitosan-based sponge rod, a chitosan-based compressed cotton swab with water absorption and expansion characteristics and hemostatic properties were prepared by mixing the chitosan solution with calcium ion solution, freeze-drying and reinforcement of the alkaline solution, and the size was similar to that of the particles for internal irradiation.

Benefits of technology

The rod provides support during the implantation process, prevents particle displacement, stops bleeding quickly, reduces postoperative complications, improves treatment effect, and has low process cost, simple preparation method and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention belongs to the field of biomedical materials, and particularly relates to a bar for assisting in internal irradiation of particles as well as a preparation method and application of the bar. The bar is a chitosan-based compressed cotton swab, the size of the bar is similar to that of the particles for internal irradiation, the bar has the water-absorbing swelling characteristic and the hemostatic characteristic, the bar has certain hardness, and it is guaranteed that the particles for internal irradiation do not deform or break in the implantation process and are completely implanted into a tumor. The preparation method of the bar comprises the following steps: mixing an aqueous solution or an aqueous solution containing calcium ions with a chitosan solution, freeze-drying, further soaking in an alkaline solution, washing to be neutral, freeze-drying again, and mechanically compressing to obtain the chitosan-based short bar. The chitosan-based short rod is similar to internal irradiation particles for radiotherapy internal irradiation in size and shape, is used as an auxiliary material for the internal irradiation particles, and is alternately arranged in a cartridge holder of a particle implantation gun together with the internal irradiation particles during use, so that the internal irradiation particles are fixed, and side reactions such as bleeding of a puncture pipeline in an operation process are prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedical materials and relates to a rod material for assisting internal irradiation particles, specifically a chitosan-based sponge material with certain hardness, water absorption and swelling properties and hemostatic properties, which is used for fixation and hemostasis of internal irradiation particles after implantation in vivo. Background Art

[0002] Internal irradiation particles such as radioactive iodine 125 ( 125 I) Particle implantation (radioactive 125 I seed implantation (RISI) brachytherapy has been increasingly widely used in clinical practice of tumors. It has the advantages of accurate positioning, less trauma, and a wide range of indications. This treatment technology has shown effectiveness in a variety of malignant tumors, such as lung cancer, liver cancer, and uveal melanoma. However, since the implantation of particles requires the precise delivery of particles into the lesion tissue through puncture or catheter, it is often accompanied by the following problems: First, bleeding caused by puncture. After puncturing into the lesion or adjacent tissue, blood vessels may be damaged, causing local bleeding; especially in areas with rich blood vessels (such as the liver, lungs, etc.) or areas with rich blood supply to the tumor, the risk of bleeding is higher, which may affect the surgical effect or aggravate the patient's condition. Second, particle displacement causes misembolism. In some cases, particle displacement may cause misembolism, and embolic materials need to be used to block the puncture path or local blood vessels.

[0003] The existing technical means generally use hemostatic materials, embolic materials or mechanical hemostasis to solve the above problems. Among them, hemostatic materials generally use coagulation powder prepared from materials such as oxidized cellulose, gelatin, chitosan, etc., which is used for local filling to promote coagulation, but these coagulation powders are mostly powdered, liquid or do not have sufficient hardness, and it is difficult to stabilize the position of particles and cannot provide sufficient support or particle fixation function; fibrin glue-type hemostatic materials are injected into gel to form embolism, which can block blood vessels or puncture paths, but the coagulation time is long, the application is cumbersome, and the operation difficulty and operation time are increased, and the particle support effect is limited. Although the use of polyvinyl alcohol particles or gelatin particles for vascular embolism through interventional technology can effectively reduce bleeding, such materials are mostly used for intravascular embolism rather than intratissue hemostasis, and cannot meet the dual needs of intratissue hemostasis and particle support. Mechanical hemostasis generally uses compression hemostasis after puncture, but it is difficult to accurately achieve in deep tissues or surgical sites, and it is not helpful for particle fixation.

[0004] Therefore, optimizing the brachytherapy process and preparing a material that has both water-absorbing and swelling properties and hemostatic functions, while also having appropriate hardness, can provide support during particle implantation, avoid particle displacement, and quickly stop bleeding to reduce postoperative complications and improve treatment outcomes, which has become an urgent problem to be solved. Summary of the invention

[0005] In view of the above problems, the present invention proposes to prepare a rod for assisting internal irradiation particles. The rod is composed of a chitosan-based compressed cotton rod with a certain hardness. The size of the rod is similar to that of the particles used for internal irradiation. It has a certain mechanical strength to facilitate surgical operations, has water absorption and expansion properties, and has hemostatic properties.

[0006] The invention discloses a preparation method for a rod material for assisting internal irradiation particles. The chitosan sponge rod has a porous structure and is formed by using a chitosan solution or mixing a calcium ion solution with a chitosan solution and then freeze-drying and shaping. The introduction of calcium ions makes the chitosan sponge rod have higher hardness and hemostatic performance. The chitosan sponge rod is in a round rod shape, which is achieved through a prefabricated model and freeze-drying shaping process. After being reinforced with an alkaline solution, the hydrophilicity of the chitosan sponge rod is enhanced, which helps to improve its compatibility with water. The alkaline solution reinforcement treatment not only increases the hydrophilicity of the chitosan sponge rod, but also reduces its water solubility, making it more suitable for use in a wet environment. The chitosan sponge rod is prepared into a short rod shape by mechanical compression, which helps to adjust its shape and size to meet specific application requirements.

[0007] The present invention adopts the following technical solutions:

[0008] The first aspect of the present invention provides a rod for assisting internal irradiation with particles, characterized in that the rod is a chitosan-based compressed cotton swab, the rod size is similar to that of the particles for internal irradiation, the rod has water absorption and swelling properties and hemostatic properties, the rod has a certain hardness, which is sufficient to support the pressure of the tools used for internal irradiation operations, ensuring that it will not deform or break during the entire implantation process, and will be implanted into the tumor in its original shape.

[0009] In the above technical solution, further, the water absorption and swelling characteristic refers to rapid water absorption within 60 seconds, and the mass after water absorption reaches 6 to 20 times that before water absorption, and the volume reaches 5 to 20 times.

[0010] In the above technical solution, further, the rod has a length of 0.5 to 10 mm and a diameter of 0.1 to 1.5 mm.

[0011] In the above technical solution, further, the hemostatic property of the rod refers to:

[0012] Physical compression hemostasis: The shape and material of the rod can compress blood vessels when applied topically, reducing or stopping bleeding;

[0013] Chemical hemostasis: The rod contains chemical components such as calcium ions that can promote blood coagulation. When it comes into contact with a wound or bleeding area, it accelerates blood coagulation by activating coagulation factors;

[0014] Biocompatible hemostasis: The rod uses chitosan as its raw material, which has good compatibility with human tissue. It will not cause rejection when used, and can promote wound healing and stop bleeding.

[0015] Absorbent hemostasis: The rod has the ability to absorb blood. By absorbing the fluid in the bleeding area, it increases the local blood concentration and thus accelerates the coagulation process.

[0016] The second aspect of the present invention provides a method for manufacturing the aforementioned rod, comprising the following steps:

[0017] (1) preparing chitosan acetic acid solution: dissolving chitosan in 0.5-3% (v / v) acetic acid solution, wherein the molecular weight of chitosan is 50-1000 KDa and the degree of deacetylation is ≥50%; heating as required during the stirring and dissolving process, and the heating temperature does not exceed 60° C.;

[0018] (2) Prepare calcium ion solution: dissolve calcium in acidic solution or deionized water, and stir to dissolve evenly;

[0019] Wherein, the calcium is one or more of calcium chloride, calcium acetate, calcium gluconate, calcium lactate, calcium malate or calcium citrate, and calcium chloride and calcium acetate are dissolved in room temperature water, or calcium gluconate and calcium lactate are dissolved in 60°C warm water, or calcium malate and calcium citrate are dissolved in acetic acid solution;

[0020] The dissolved calcium ion solution is mixed evenly with the chitosan solution in step (1);

[0021] (3) pouring the solution in step (1) into a round bar mold or pouring the solution in step (2) into a round bar mold, standing to remove bubbles and then freezing, and freeze-drying the frozen solution to a constant weight to obtain a sponge-like solid chitosan-based sponge;

[0022] (4) soaking the initially freeze-dried sponge in an alkaline solution, and then washing with deionized water until the pH is neutral;

[0023] (5) freezing the solid again, and performing a secondary freeze-drying process after the solid is frozen;

[0024] (6) The dried chitosan sponge is mechanically compressed into a short rod shape.

[0025] The chitosan sponge stick is 0.5 to 10 mm long and 0.1 to 1.5 mm in diameter.

[0026] In the above technical solution, further, in the chitosan acetic acid solution in step (1), the concentration of chitosan is 10 to 200 g / L.

[0027] In the above technical solution, further, in the calcium ion solution in step (2), the concentration of calcium ions is 0 to 100 mmol / L.

[0028] In the above technical solution, further, in step (3) and step (5), the freezing environment is -4 to -200°C, and the freezing is 0.5 to 24 hours; the freeze drying is vacuum freeze drying at -65°C to -20°C in a freeze dryer for 2 to 48 hours.

[0029] In the above technical scheme, further, in step (4), the alkaline solution is sodium hydroxide, potassium hydroxide or lithium hydroxide / urea mixed solution, the concentration of sodium hydroxide, potassium hydroxide or lithium hydroxide solution is 1-5% (m / v), and the concentration of urea is 5-10% (m / v); the soaking time is 0.5-4h; the deionized water washing number is ≥3 times, and the pH neutrality refers to 7.0-7.5.

[0030] A third aspect of the present invention provides the use of the aforementioned rod material for assisting fixation of internally irradiated particles in vivo; and / or for hemostasis during implantation of internally irradiated particles.

[0031] In the above technical solution, further, the rods and the internal irradiation particles are alternately discharged into the magazine of the particle implantation gun in the order of "0 to 2 rods" - "1 internal irradiation particle" - "0 to 2 rods", and are placed repeatedly in sequence, and implanted into the tumor in this order. It plays a role in fixing the internal irradiation particles and preventing the occurrence of side reactions such as bleeding in the puncture line during the operation.

[0032] Beneficial effects of the present invention:

[0033] 1. The external dimensions of the auxiliary rod of the present invention are the same as those of the internal irradiation particles, and the auxiliary fixation and hemostasis effects of the rod can be exerted by alternately implanting the rod and the internal irradiation particles without changing the existing clinical operation path.

[0034] 2. In view of the problems of puncture damage to blood vessels, particle migration, bleeding, and accidental thrombosis that occur during the implantation of internal irradiation particles, the present invention proposes for the first time that the rod of the present invention is used as an auxiliary in the implantation of internal irradiation particles to stop bleeding and fix the internal irradiation particles. The rod of the present invention is similar in size to the internal irradiation particles and can be implanted alternately with the internal irradiation particles. Since the rod of the present invention has a certain hardness, it can be successfully implanted into the body through an injection needle without deformation or breakage during the implantation process. At the same time, the rod of the present invention has both hemostatic and swelling properties. After implantation into the body, after the needle tube is withdrawn, it quickly absorbs blood / tissue fluid and swells, filling the needle tube channel, assisting in fixing the particles, and quickly stopping bleeding.

[0035] 3. The process cost of the present invention is low and the preparation method is simple. No organic solvents and toxic cross-linking agents are used, which reduces environmental pollution. Calcium ions are introduced during the preparation process to increase the strength of the rod, so that it will not deform or break during the implantation process, and can quickly absorb blood / tissue swelling. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Schematic diagram of the rod for internal irradiation particle assistance without calcium ions prepared in Example 1 of the present invention before and after water absorption, wherein the left side is before water absorption and the right side is after water absorption;

[0037] Figure 2 This is a scanning electron microscope image of a rod material for internal irradiation particle assistance without calcium ions prepared in Example 1 of the present invention;

[0038] Figure 3 This is a scanning electron microscope image of the calcium ion-containing internal irradiation particle auxiliary rod prepared in Example 2 of the present invention;

[0039] Figure 4 This is a graph showing the water absorption test data of the rod material for internal irradiation particle assistance prepared in Example 3 of the present invention;

[0040] Figure 5 This is a graph showing the water absorption test data of the rod material for internal irradiation particle assistance prepared in Example 4 of the present invention;

[0041] Figure 6 Schematic diagram comparing the coagulation effects of Example 1 of the present invention and commercially available products, and a light absorption data diagram after washing of unabsorbed blood, wherein each picture shows, from left to right, left: commercially available gelatin sponge hemostatic material, middle: commercially available chitosan sponge hemostatic material, right: rod for internal irradiation particle assistance prepared in Example 1 of the present invention;

[0042] Figure 7 Schematic diagram of the rod usage process. DETAILED DESCRIPTION

[0043] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.

[0044] In the following description, we will combine the diagrams in the actual cases of the present invention to provide a detailed and complete description of the technical solution. It is worth noting that the cases only represent some implementation methods of the present invention, not all of them.

[0045] Example 1

[0046] 1) Weigh 2.0 g of chitosan powder, wherein the chitosan has a deacetylation degree of 95% and a molecular weight of 200 KDa, and dissolve the chitosan in 100 mL of 1% (v / v) acetic acid aqueous solution, and stir thoroughly to dissolve to obtain a 2% (w / v) chitosan solution.

[0047] 2) Pour the chitosan solution in 1) into a round bar mold, let it stand to remove bubbles, and then freeze it in a -20°C refrigerator. Take out the frozen chitosan solution, place it in a vacuum environment of 5-10Pa at -50°C for freeze drying, and the drying time is 24 hours.

[0048] 3) Weigh 4.0 g of sodium hydroxide solid and dissolve it in 100 mL of deionized water to prepare a 4% (m / v) alkaline solution. Soak the dried chitosan sponge in the alkaline solution for 2 hours, then replace it with deionized water, changing the water every half an hour until the pH value is 7.0-7.5.

[0049] 4) The sponge in 3) is placed in a -20°C refrigerator for freezing. The frozen sponge is taken out and placed in a -50°C vacuum environment of 5 to 10 Pa for freeze drying.

[0050] 5) The dried sponge was compressed into a rod with a length of 4.5 mm and a diameter of 0.8 mm by mechanical compression.

[0051] 6) After high-pressure sterilization of the above-mentioned rods, the hemostatic performance was compared with that of commercially available products. Figure 6 The results of the comparison of the hemostatic performance of the rod for internal irradiation particle assistance in Example 1 in vitro and the commercially available products are shown. The results show that when equal amounts of fresh rabbit blood are added to the three groups of samples, the rod of the present invention can absorb all the blood within 60 seconds and remain unchanged for 5 minutes. After 5 minutes, the material is removed and the amount of residual blood is minimal. Therefore, the rod of the present invention shows significant advantages in coagulation performance over the commercially available gelatin hemostatic materials and chitosan hemostatic materials.

[0052] Figure 1 This is a schematic diagram of the rod for internal irradiation particle assistance in Example 1 of the present invention before and after water absorption. Within 60 seconds, the rod prepared in Example 1 can quickly absorb water and expand, and the mass after water absorption reaches 16 times that before water absorption.

[0053] Example 2

[0054] 1) Weigh 2.0 g of chitosan powder, wherein the chitosan has a deacetylation degree of 95% and a molecular weight of 200 KDa, and dissolve the chitosan in 100 mL of 1% (v / v) acetic acid aqueous solution, and stir thoroughly to dissolve to obtain a 2% (w / v) chitosan solution.

[0055] 2) Weigh 1.47 g CaCl 2·2H 2 Dissolve O in 10 mL of water to prepare a 1 mol / L solution, then take 0.2 mL and add it to the solution in 1) and stir thoroughly.

[0056] 3) Pour the mixed solution in 2) into a round bar mold, let it stand to remove bubbles, and then freeze it in a -20°C refrigerator. Take out the frozen chitosan solution, place it in a -50°C vacuum environment of 5-10Pa for freeze drying, and the drying time is 24 hours.

[0057] 4) Weigh 4.0 g of sodium hydroxide solid and dissolve it in 100 mL of deionized water to prepare a 4% (m / v) alkaline solution. Soak the dried chitosan sponge in the alkaline solution for 2 hours, then replace it with deionized water, changing the water every half an hour until the pH value is 7.0-7.5.

[0058] 5) The sponge prepared in 4) is placed in a -20°C refrigerator for freezing. The frozen sponge is taken out and placed in a -50°C vacuum environment of 5 to 10 Pa for freeze drying.

[0059] 6) The dried sponge was compressed mechanically into a short rod with a length of 4.5 mm and a diameter of 0.8 mm.

[0060] The rods prepared in Example 1 and Example 2 are respectively as follows Figure 2 and Figure 3 As shown, after the introduction of calcium ions, the spatial structure and pore structure of the sponge scaffold are maintained, calcium substances are obviously attached to the inner surface of the sponge pores, the hardness of the sponge increases, and it is less likely to deform or break during use. It is sufficient to support the pressure of the tools used for internal irradiation operations and be completely implanted into the tumor; and the rod prepared in Example 2 still has good water absorption and expansion properties.

[0061] Example 3

[0062] 1) Weigh 1.0, 2.0, 3.0, 4.0 and 5.0 g of chitosan powder, wherein the chitosan has a deacetylation degree of 95% and a molecular weight of 200 KDa. Dissolve the chitosan in 100 mL of 1% (v / v) acetic acid aqueous solution, and stir thoroughly to dissolve to obtain 1%, 2%, 3%, 4% and 5% (w / v) chitosan solutions, respectively.

[0063] 2) Pour the chitosan solution in 1) into round bar molds, let it stand to remove bubbles, and then freeze it in a -20°C refrigerator. Take out the frozen chitosan solution, place it in a vacuum environment of 5-10Pa at -50°C for freeze drying, and the drying time is 24 hours.

[0064] 3) Weigh 4.0 g of sodium hydroxide solid and dissolve it in 100 mL of deionized water to prepare a 4% (m / v) alkaline solution. Soak the dried chitosan sponge in the alkaline solution for 2 hours, then replace it with deionized water, changing the water every half an hour until the pH value is 7.0-7.5.

[0065] 4) The sponge in 3) is placed in a -20°C refrigerator for freezing. The frozen sponge is taken out and placed in a -50°C vacuum environment of 5 to 10 Pa for freeze drying.

[0066] 5) Compress the dried sponge into a short stick shape by mechanical compression.

[0067] 6) Weigh the weight of the sponge sticks prepared with the chitosan solutions of 1%, 2%, 3%, 4%, and 5% (w / v) above and record them as W 0 , and then immerse them in deionized water respectively. After they are saturated with water, take them out and gently absorb the unabsorbed water on the edge with absorbent paper, weigh them again and record them as W 1 The water absorption rate is calculated according to the following formula:

[0068] Water absorption rate = (W 1 -W 0 ) / W 0

[0069] 7) Plot the above water absorption data to obtain Figure 4 The results showed that within the 5% concentration range, the higher the chitosan concentration, the lower the water absorption rate. When the chitosan concentration was 1% (w / v), the water absorption rate was close to 20 times; when the chitosan concentration increased to 5%, the water absorption rate dropped to 6 times.

[0070] Example 4

[0071] 1) Weigh 2.0 g of chitosan powder, wherein the chitosan has a deacetylation degree of 95% and a molecular weight of 200 KDa, and dissolve the chitosan in 100 mL of 1% (v / v) acetic acid aqueous solution, and stir thoroughly to dissolve to obtain a 2% (w / v) chitosan solution.

[0072] 2) Weigh 1.47, 3.675, 7.35, and 36.75 g of CaCl respectively 2 ·2H 2 O was dissolved in 10 mL of water to prepare solutions of 1, 2.5, 5, and 25 mol / L, respectively. 0.2 mL of the above calcium chloride solution was added to the solution in 1) and stirred thoroughly. Another 0.2 ml of deionized water was added to the solution in 1) as a control group without calcium.

[0073] 3) Pour the 5 mixed solutions in 2) into a round bar mold, let it stand to remove bubbles, and then freeze it in a -20°C refrigerator. Take out the frozen chitosan solution, place it in a vacuum environment of 5-10Pa at -50°C for freeze drying, and the drying time is 24 hours.

[0074] 4) Weigh 4.0 g of sodium hydroxide solid and dissolve it in 100 mL of deionized water to prepare a 4% (m / v) alkaline solution. Soak the dried chitosan sponge in the alkaline solution for 2 hours, then replace it with deionized water, changing the water every half an hour until the pH value is 7.0-7.5.

[0075] 5) The sponge prepared in 4) is placed in a -20°C refrigerator for freezing. The frozen sponge is taken out and placed in a -50°C vacuum environment of 5 to 10 Pa for freeze drying.

[0076] 6) Compress the dried sponge into a short stick shape by mechanical compression.

[0077] 7) Weigh the chitosan sponge sticks with final calcium concentrations of 0, 2, 5, 10, and 50 mM, respectively, and record their weights as W. 0 , and then immerse them in deionized water respectively. After they are saturated with water, take them out and gently absorb the unabsorbed water on the edge with absorbent paper, weigh them again and record them as W 1 The water absorption rate is calculated according to the following formula:

[0078] Water absorption rate = (W 1 -W 0 ) / W 0

[0079] Plotting the above water absorption data gives Figure 5 The results showed that the calcium ion concentration within the range of 50mM did not affect the water absorption rate of the chitosan sponge rod.

[0080] Example 5

[0081] 1) The chitosan sponge sticks obtained in Examples 1 and 2 were sterilized by high pressure steam and then subjected to a hemostasis test.

[0082] 2) Rats were used as experimental animals. The experiment was divided into 3 groups, namely the cotton gauze group, the calcium-free chitosan sponge group of Example 1, and the calcium-containing chitosan sponge group of Example 2. The rats were anesthetized and fixed on the operating frame with the abdomen facing up. After the abdominal hair was removed and cleaned, a wound about 1 cm long and 0.2 cm deep was cut in the abdomen with a blade. The above 3 groups of hemostatic materials were immediately used to cover the wound, and gently pressed to stop bleeding. During the operation, the bleeding of the wound surface of the rats was observed every 10 seconds and the clotting time was recorded to evaluate the hemostatic effect of the chitosan sponge stick on the surgical incision trauma. The results are listed in the table below:

[0083]

[0084] The above test results prove that the chitosan sponge sticks prepared according to Example 1 and Example 2 have excellent hemostatic effects, and the hemostatic effect of the chitosan sponge stick containing calcium is better.

[0085] Example 6

[0086] 1) Experimental group: The rods prepared in Example 1, with a size of 4.5 mm in length and 0.8 mm in diameter, were alternately discharged into the magazine of the particle implantation gun with titanium shell particles (4.5 mm in length and 0.8 mm in diameter) without drug loading, and sequentially implanted into the lung tissue of anesthetized rats. Each rat was implanted with 2 channels, and 4 auxiliary rods + 3 titanium shell particles were alternately implanted in each channel. A total of 6 rats.

[0087] Control group: Unloaded titanium shell particles (4.5 mm in length and 0.8 mm in diameter) were routinely discharged into the cartridge of the particle implantation gun and implanted into the lung tissue of anesthetized rats according to clinical procedures. Two channels were implanted per rat, with three titanium shell particles per channel. A total of six rats were included.

[0088] 2) CT scans were performed to observe the position of the particles in the lungs before and after the implantation, and 1 day, 7 days, and 28 days after implantation. The results showed that the titanium shell particles implanted in all rats in the experimental group (a total of 36 particles) did not shift; however, 9 titanium shell particles in the control group shifted, which was significantly different from the experimental group. The rods in the experimental group did not deform or break during the implantation process.

Claims

1. A rod material for internal irradiation particle assistance, characterized in that: The rod is a chitosan-based compressed cotton stick, the size of the rod is similar to that of the particles used for internal irradiation, the rod has water absorption and swelling properties and hemostatic properties, and has a certain hardness to ensure that the rod will not deform or break during the internal irradiation particle implantation process and can be completely implanted into the tumor.

2. The rod material for internal irradiation particle assistance according to claim 1, characterized in that: The water absorption and swelling property refers to rapid water absorption within 60 seconds, and the mass after water absorption reaches 6 to 20 times the mass before water absorption, and the volume reaches 5 to 20 times.

3. The rod material for internal irradiation particle assistance according to claim 1, characterized in that: The rod has a length of 0.5 to 10 mm and a diameter of 0.1 to 1.5 mm.

4. The rod material for internal irradiation particle assistance according to claim 1, characterized in that: The method for making the rod comprises the following steps: (1) preparing chitosan acetic acid solution; (2) preparing a calcium ion solution: dissolving one or more of calcium chloride, calcium acetate, calcium gluconate, calcium lactate, calcium malate or calcium citrate in deionized water at room temperature or heated deionized water or acetic acid solution to stably dissolve the calcium ion solution; and uniformly mixing the dissolved calcium ion solution with the chitosan solution in step (1); (3) pouring the solution obtained in step (1) or (2) into a mold, freezing, and freeze-drying until constant weight is reached to obtain a chitosan-based sponge; (4) soaking the sponge in an alkaline solution for reinforcement, and then washing with deionized water until the pH is neutral; (5) freezing the solid again and performing a secondary freeze-drying process; (6) The dried chitosan-based sponge is mechanically compressed into a short rod shape.

5. The rod material for internal irradiation particle assistance according to claim 4, characterized in that: In the chitosan acetic acid solution of step (1), the concentration of chitosan is 10 to 200 g / L.

6. The rod material for internal irradiation particle assistance according to claim 4, characterized in that: In the calcium ion solution of step (2), the concentration of calcium ions is 0 to 100 mmol / L.

7. The rod material for internal irradiation particle assistance according to claim 4, characterized in that: In step (3) and step (5), the freezing environment is -4 to -200°C and the freezing time is 0.5 to 24 hours; The freeze drying is performed by vacuum freeze drying at -65°C to -20°C in a freeze dryer for 2 to 48 hours.

8. The rod material for internal irradiation particle assistance according to claim 4, characterized in that: In step (4), the alkaline solution is sodium hydroxide, potassium hydroxide or a lithium hydroxide / urea mixed solution, the concentration of the sodium hydroxide, potassium hydroxide or lithium hydroxide solution is 1-5% (m / v), and the concentration of urea is 5-10% (m / v); The soaking time is 0.5 to 4 hours.

9. The use of the rod material for internal irradiation particle assistance according to claim 1, characterized in that: Used to assist in the fixation of internal irradiation seeds in the body; and / or used for hemostasis during the implantation of internal irradiation seeds.

10. The use of the auxiliary rod according to claim 9, characterized in that: The rods and internally irradiated particles are alternately discharged into the magazine of the particle implantation gun in the order of "0 to 2 rods" - "1 internally irradiated particle" - "0 to 2 rods", and are repeatedly placed.